Early Postnatal IGF-1 and IGFBP-1 Blood Levels in Extremely Preterm Infants: Relationships with Indicators of Placental Insufficiency and with Systemic Inflammation - Leviton, Alan; Allred, Elizabeth N.; Fichorova, Raina N.; VanderVeen, Deborah K.; O'Shea, T. Michael; Kuban, Karl; Dammann, Olaf; for the ELGAN Study Investigators (American Journal of Perinatology, 2019)
Objective To evaluate to what extent indicators of placenta insufficiency are associated with low concentrations of insulin-like growth factor 1 (IGF-1) and IGF-1–binding protein-1 (IGFBP-1) in neonatal blood, and to what extent the concentrations of these growth factors are associated with concentrations of proteins with inflammatory, neurotrophic, or angiogenic properties.Study Design Using multiplex immunoassays, we measured the concentrations of IGF-1 and IGFBP-1, as well as 25 other proteins in blood spots collected weekly from ≥ 880 infants born before the 28th week of gestation, and sought correlates of concentrations in the top and bottom quartiles for gestational age and day the specimen was collected.Results Medically indicated delivery and severe fetal growth restriction (sFGR) were associated with low concentrations of IGF-1 on the first postnatal day and with high concentrations of IGFBP-1 on almost all days. Elevated concentrations of IGF-1 and IGFBP-1 were accompanied by elevated concentrations of many other proteins with inflammatory, neurotrophic, or angiogenic properties.Conclusion Disorders associated with impaired placenta implantation and sFGR appear to account for a relative paucity of IGF-1 on the first postnatal day. Elevated concentrations of IGF-1 and especially IGFBP-1 were associated with same-day elevated concentrations of inflammatory, neurotrophic, and angiogenic proteins.
Keywords: IGF-1; neurotrophic factors; cytokines; inflammation; infant; blood; angiogenic; placenta insufficiency; fetal growth restriction; preeclampsia